Demonstrative Consumption and Developmental Components: The Analysis of the Effect of Demonstrative Consumption on Development-Oriented Components Among Citizens With Higher Education Aged 20 To 65 in Zanjan - Fatemeh Bayat; Shapour Behyan; asghar mohammadi (توسعه اجتماعی)
The aim of this study was to analyze the effect of demonstrative consumption on the components of sustainable development. In a survey study in 2020, 502 citizens with higher education aged 20 to 65 in Zanjan 463865 people were selected from a statistical population by sampling multi-stage clusters. The research tool is a questionnaire (Cronbach's alpha> 0.80). Data were analyzed in SPSS and PLS statistical software at the significance level of P <0.05 and error of 0.95. According to descriptive findings, demonstrative consumption status (average=111.23) and the status of development-oriented components (average=246.99) they are at an intermediate level. Results show a strong and inverse correlation between demonstrative consumption and developmental components (r = -0.567 & P= 0.01). Development in all three dimensions of awareness (r =-0.208 & P=0.01), attitude (r= -0.338 & P= 0.01) and behavior (r =-0.609 & P= 0.01) Showed the circuit. Regression analysis explained part of the variance of developmental components in society by demonstrative consumption dimensions (R2= 0.403). Findings showed an inverse correlation between socio-economic class and demonstrative consumption (P=0.025) but it did not show a correlation with development-oriented components (P = 0.775). The measurement model and the structural model confirm the effects. Overall, the results showed the effect of demonstrative consumption pattern on developmental components. Therefore, the most important development-oriented strategies should be to reform the consumption patterns of society.